2018
DOI: 10.18632/aging.101549
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant modifications induced by the new metformin derivative HL156A regulate metabolic reprogramming in SAMP1/kl (-/-) mice

Abstract: Aging is characterized by a reduced ability to defend against stress, an inability to maintain homeostasis, and an increased risk of disease. In this study, a metabolomics approach was used to identify novel metabolic pathways that are perturbed in a mouse model of accelerated aging (SAMP1/kl-/-) and to gain new insights into the metabolic associations of the metformin derivative HL156A. Extensive inflammation and calcification were observed in the tissues of the SAMP1/kl-/- mice with premature aging. In mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Metformin is recommended as the first-line treatment for T2DM patients, but should not be used in those with severe liver or kidney problems 6. The mechanism of action of metformin is that it could suppress the hepatic glucose production, and then lead to the reduction in hemoglobin A1c (HbA1c) and fasting plasma-glucose (FPG) 710. However, the multiple pathogenetic disturbances present in T2DM dictate that the combined application of multiple anti-diabetic medications is needed to maintain normoglycaemia 2…”
Section: Introductionmentioning
confidence: 99%
“…Metformin is recommended as the first-line treatment for T2DM patients, but should not be used in those with severe liver or kidney problems 6. The mechanism of action of metformin is that it could suppress the hepatic glucose production, and then lead to the reduction in hemoglobin A1c (HbA1c) and fasting plasma-glucose (FPG) 710. However, the multiple pathogenetic disturbances present in T2DM dictate that the combined application of multiple anti-diabetic medications is needed to maintain normoglycaemia 2…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our results, the mTOR inhibitor rapamycin promoted the generation of memory T cells (6), suggesting that inhibition of glycolytic metabolism enhances the differentiation of memory T cells. The discrepancy in the effects caused by either metformin or IM156 may be related to the strength of AMPK activation and ability of cell penetration (1220). In a previous study, the mode of action of IM156 was described as activation of AMPK (111213) and/or energy deprivation as a result of inhibition of mitochondrial oxidative phosphorylation (1011).…”
Section: Discussionmentioning
confidence: 99%
“…The best-known mechanism of IM156 is AMPK activation. IM156-mediated AMPK activation ameliorates peritoneal fibrosis (12), liver fibrosis (20), and renal fibrosis (13) and prevents the growth of human oral cancer (11). In our study, we showed that IM156 restricts proper memory differentiation after viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…MEFs were derived and cultured from SAMP1/kl+/+ and SAMP1/kl-/- 13-day-old embryos that were obtained by mating SAMP1/kl+/- mice with SAMP1/kl+/- mice [32] and maintained in Dulbecco’s Modified Eagle’s Medium (DMEM, Gibco, NY) containing gentamycin, glutamine, MEM nonessential amino acids, 2-mercaptoethanol, and 10% fetal bovine serum (FBS, Gibco, NY). The human embryonic kidney 293 cell line and MEFs isolated from wild-type or klotho knockout mice were grown in DMEM supplemented with 10% FBS, 100 units/ml penicillin, and 100 μg/ml streptomycin (Invitrogen, CA) in a humidified 5% CO 2 /95% air atmosphere at 37°C.…”
Section: Methodsmentioning
confidence: 99%